2021
DOI: 10.3389/fpsyg.2021.583743
|View full text |Cite
|
Sign up to set email alerts
|

Neuroscience of Object Relations in Health and Disorder: A Proposal for an Integrative Model

Abstract: Recent advances in the neuroscience of episodic memory provide a framework to integrate object relations theory, a psychoanalytic model of mind development, with potential neural mechanisms. Object relations are primordial cognitive-affective units of the mind derived from survival- and safety-level experiences with caretakers during phase-sensitive periods of infancy and toddlerhood. Because these are learning experiences, their neural substrate likely involves memory, here affect-enhanced episodic memory. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 175 publications
(443 reference statements)
0
8
0
Order By: Relevance
“…Some other studies, such as the study by Mahmoudi et al (2018) have not shown a difference in the perception of social support and self-compassion between patients with MS and the general population ( 28 ). Despite these differences, some neuroscience studies have confirmed that in illness and health, the intrapsychic and interpersonal realms of individuals create each other ( 1 ). The issue of communications between self and others seems to be more complex in patients with MS and more detailed explanations are needed of the effect of the disease on the basic personality traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other studies, such as the study by Mahmoudi et al (2018) have not shown a difference in the perception of social support and self-compassion between patients with MS and the general population ( 28 ). Despite these differences, some neuroscience studies have confirmed that in illness and health, the intrapsychic and interpersonal realms of individuals create each other ( 1 ). The issue of communications between self and others seems to be more complex in patients with MS and more detailed explanations are needed of the effect of the disease on the basic personality traits.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sclerosis ( 1 ) is one of the most common neurological disorders and a leading cause of disability. According to the latest global atlases, about 2.8 million people in the world (35.9 per 100,000 population) have the disease, with an average age of 32 years.…”
mentioning
confidence: 99%
“…This gap led to the rise of brain organoid technology-a cutting-edge in vitro paradigm emulating the sophisticated architecture and functions of the human brain [7,8]. These pioneering methodologies have harnessed the self-organizing propensities of PSCs, guiding them to mimic the early milestones of brain development [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing these limitations, brain organoid technology has emerged as a revolutionary approach. It leverages the self-organizing capabilities of iPSCs, closely mimicking key milestones in early brain development (9, 10, 11, 12, 13). Emphasizing the significance of this shift towards three-dimensional (3D) modelling, several distinct organoid models have been developed, each targeting specific aspects of brain functionality and spatial organization.…”
Section: Introductionmentioning
confidence: 99%